Budowa modelu biznesowego przedsiębiorstw w procesach fuzji i przejęć - Białowąs, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the article, the author presented main models containing principles of establishing holding and concerns. It is based on Polish law regulations. The text presents the main problems connected with this process. The author tried to describe principles of redesigned main business model of organization established in merger process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 21-27